1989
DOI: 10.1001/jama.1989.03430020069030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 100% Oxygen on Performance of Professional Soccer Players

Abstract: Supplemental oxygen is currently widely utilized in conjunction with athletic competition. To assess the utility of this practice, 12 professional soccer players performed two bouts of exhaustive exercise separated by 5 minutes of rest ("recovery period"). During the recovery period, the subjects breathed either room air or 100% oxygen, assigned by randomized, double-blind design. The entire procedure was repeated on each subject using the opposite gas. The administration of enriched oxygen during the recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The ergogenic effect on peak power output was considered to be negligible in most competitive and training settings [38]. Others have found that oxygen supplementation (F i O 2 = 0.55-1.00) during recovery from intermittent sprinting neither enhances subsequent performance nor alters oxygen uptake ( _ VO 2 ), heart rate or ventilation during submaximal or maximal exercise [45][46][47].…”
Section: Hyperoxia During Recovery From Intermittent Exercisementioning
confidence: 99%
“…The ergogenic effect on peak power output was considered to be negligible in most competitive and training settings [38]. Others have found that oxygen supplementation (F i O 2 = 0.55-1.00) during recovery from intermittent sprinting neither enhances subsequent performance nor alters oxygen uptake ( _ VO 2 ), heart rate or ventilation during submaximal or maximal exercise [45][46][47].…”
Section: Hyperoxia During Recovery From Intermittent Exercisementioning
confidence: 99%
“…Although the use of oxygen during exercise appears to be beneficial in long‐term exercise (Weltman, Katch, Sady, 1978; Adams & Welch, 1980; Welch, 1982), its effects when administered during recovery alone or during short‐term intensive intervals are controversial (Welch, 1982; Yamaji & Shephard, 1985; Winter, Snell, Stray‐Gundersen, 1989; Robbins et al., 1992; Maeda & Yasukouchi, 1997). The results of the present study suggested that the breathing of supplemental oxygen in exercise consisted of short‐term high intensity intervals did neither hasten recovery nor delay [H + ] nor lactate accumulation.…”
Section: Perspectivesmentioning
confidence: 99%
“…Previous studies suggest that the breathing of supplemental oxygen in exercise consisting of short‐term high‐intensity intervals neither hastens recovery nor delays [H + ] or lactate accumulation (Nummela et al, 2002). Although the use of oxygen appears to be beneficial in long‐term exercise (Weltman et al, 1978; Adams & Welch, 1980), its effects when administered during recovery alone or during short‐term intensive intervals are controversial (Welch, 1982; Yamaji & Shephard, 1985; Winter et al, 1989; Robbins et al, 1992; Maeda & Yasukouchi, 1997).…”
mentioning
confidence: 99%